The effect of portfolio approach and genre-based pedagogy on listening comprehension of Iranian EFL learners - Mahmood Reza Atai (Teaching English Language, 2012)
This study was conducted to examine whether raising the awareness of EFL listeners about the generic structure of news through portfolio approach may significantly enhance the subjects’ listening comprehension performance. To this end, around 97 advanced Iranian EFL learners participated in this study. The first experimental group received explicit teaching of generic structures of the genre of news. The participants in the second experimental group (i.e. portfolio assessment group) were helped to develop their awareness of the genre of news through completing their portfolios. The subjects in the control group listened to the news and completed some conventional activities. Instrumentation included a listening comprehension test and an attitude questionnaire. The results showed that explicit teaching of the generic structures of the genre of news as well as the application of portfolio assessment did not have any significant effect on listening comprehension performance of EFL listeners. It is concludes that only skilled listeners may benefit from genre-based pedagogy and portfolio assessment.